2013
DOI: 10.1093/molehr/gat056
|View full text |Cite
|
Sign up to set email alerts
|

NLRP7 or KHDC3L genes and the etiology of molar pregnancies and recurrent miscarriage

Abstract: Women with mutation in both alleles of the NLRP7 or C6orf221/KHDC3L genes are predisposed to diploid biparental moles, but it has also been suggested that mutation in these genes can predispose to diploid androgenetic or triploid moles and to other kinds of reproductive wastage. We have investigated the association between molar pregnancy and recurrent miscarriages regarding changes in the NLRP7 and C6orf221/KHDC3L genes. Our study group can be divided into three sub-cohorts: (i) women having had at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Two studies (Huang et al, 2013, Messaed et al, 2011 polymorphisms. In contrast, two further studies (Andreasen et al, 2013, Manokhina et al, 2013 identified no disease-causing mutations in NLRP7 in women with RPL and similarly Aghajanova et al (Aghajanova et al, 2015) found no mutations in NLRP7, NLR family, pyrin domain-containing 2 (NLRP2) or KHDC3-like protein, subcortical maternal complex member (KHDC3L) (C6orf221).…”
Section: Recurrent Molar Pregnanciesmentioning
confidence: 97%
See 2 more Smart Citations
“…Two studies (Huang et al, 2013, Messaed et al, 2011 polymorphisms. In contrast, two further studies (Andreasen et al, 2013, Manokhina et al, 2013 identified no disease-causing mutations in NLRP7 in women with RPL and similarly Aghajanova et al (Aghajanova et al, 2015) found no mutations in NLRP7, NLR family, pyrin domain-containing 2 (NLRP2) or KHDC3-like protein, subcortical maternal complex member (KHDC3L) (C6orf221).…”
Section: Recurrent Molar Pregnanciesmentioning
confidence: 97%
“…and C6orf221 mutations in women with RPL (Aghajanova et al, 2015, Andreasen et al, 2013, Manokhina et al, 2013.…”
Section: Recurrent Molar Pregnanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study published in 2017 suggested that the father's occupational profession may be a risk factor in the development of HM. 14,19,[23][24][25][26][27][28] The diagnosis of hydatidiform mole is made by evaluation of beta human chorionic gonadotropin (beta HCG), ultrasonography imaging (USG) and histopathological examination of the abortion or termination material. There is no predictive laboratory test for the early diagnosis of HM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of patients with familial recurrent hydatidiform moles identified 2 candidate genes called NLRP7 and KHDC3L that are located on chromosome 19 and 6, respectively. [ 19 , 20 ] To date, approximately 50 NLRP7 mutations and 4 KHDC3L mutations have been uncovered in familial molar pregnancy patients in either homozygous or compound heterozygous fashion. [ 21 ] The cytoplasmic NLRP7 protein is a member of the CATERPILLER protein family with implications in inflammation, apoptosis and innate immunity.…”
Section: Discussionmentioning
confidence: 99%